2021
DOI: 10.1292/jvms.20-0681
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hemoplasmas and <i>Bartonella</i> species in client-owned cats in Beijing and Shanghai, China

Abstract: A year-round molecular epidemiological survey (2017 to 2018) was conducted on three hemoplasmas and two Bartonella species with zoonotic potential in client-owned cats in Beijing and Shanghai. Among 668 specimens, the overall hemoplasma-positive rate was 4.9% (3.4% for Candidatus Mycoplasma haemominutum, 0.9% for Mycoplasma haemofelis and 1.2% for Candidatus Mycoplasma turicensis). The overall Bartonella-positive rate was 8.5% (4.8% for B. henselae and 4.3% for B. clarridgeiae). Age, breed, ectoparasiticide us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(34 reference statements)
3
13
0
Order By: Relevance
“…In the current study, B. henselae-seropositive cats were significantly older than B. henselae-seronegative cats. This is consistent with previous studies suggesting that older cats are more commonly infected with B. henselae, possibly due to the fact that they have more time to be exposed to the microorganism [6,18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, B. henselae-seropositive cats were significantly older than B. henselae-seronegative cats. This is consistent with previous studies suggesting that older cats are more commonly infected with B. henselae, possibly due to the fact that they have more time to be exposed to the microorganism [6,18].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, younger cats, especially those under 2 years of age, are more likely to present with bacteraemia compared to older cats, while the latter appear to be more likely to become seropositive compared to the former [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Cats with outdoor access are more likely to become infected due to increased access to flea-infested environments [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ]. Similarly, multi-cat households are a risk factor for Bartonella infection due to the increased number of potential hosts (other infected cats) and vectors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 16.13% of the cats were positive for Mycoplasma spp. with CMhm (8.6%) more frequent than Mhf (6.45%), similar to previous studies conducted in Thailand (Do et al, 2020(Do et al, , 2021Kaewmongkol et al, 2020), South Korea (Hwang et al, 2016) and China (Kaewmongkol et al, 2017;Liu et al, 2016;Zhang et al, 2021). Moreover, CMhm was the only Mycoplasma species detected in fleas from cats (7.53%), in line with what was previously described in UK and Australia (Barrs et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…CMt infection was first reported in Switzerland in 2005 [ 19 ]. CMhm has the highest prevalence worldwide and the prevalence of Mhf and CMt is similar [ 1 3 , 5 , 6 ]; the prevalence of CMhm , Mhf , and CMt is 8.5–46.7%, 0.5–21.3%, and 1–10%, respectively [ 2 , 3 , 6 ]. Although CMhm is known to be more common than Mhf , no studies in Korea have compared the prevalence of these 3 species.…”
Section: Discussionmentioning
confidence: 99%
“…Feline hemotropic mycoplasmosis (hemoplasmosis) is primarily associated with 3 hemotropic Mycoplasma species that attach themselves to the surface of red blood cells (RBCs) in cats: Mycoplasma haemofelis ( Mhf ), Candidatus Mycoplasma haemominutum ( CMhm ), and Candidatus Mycoplasma turicensis ( CMt ) [ 1 6 ]. Molecular studies have demonstrated the existence of Mhf and CMhm species since 2007 and CMt species since 2017 in feral cats in Korea [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%